Cortical modulation of transmission in spinal reflex pathways of man. - Iles, J F (1992)
1. The motor actions in the lower limb of transcranial electrical stimulation of the motor cortex have been studied in sitting human subjects. 2. Cortical stimulation induced a short latency inhibition of H reflexes evoked in soleus motoneurones both at rest and during small voluntary contractions of soleus. 3. Spatial interaction between cortical inhibition of soleus motoneurons and inhibition evoked through identified spinal reflex machinery was investigated. 4. Interactions were found between cortically evoked inhibition and spinal Ia reciprocal inhibition, group I non-reciprocal inhibition and higher threshold components of longer latency reciprocal inhibition (D1 and D2 inhibitions). 5. Interactions were facilitatory when cortical and spinal inhibitory actions were weak and reversed to occlusion when both actions were strong. 6. It is concluded that the corticospinal pathway converges on the interneurones which subserve Ia reciprocal, group I non-reciprocal, D1 and D2 inhibition of soleus motoneurones. 7. No significant interaction was found under the present experimental conditions between cortical stimulation and group Ia-Ia presynaptic inhibition of soleus afferents. 8. The statistical significance of spatial interactions observed with H reflex conditioning was investigated using a control experiment.